17.1: Invited Paper: Closing in on Rec. 2020: How Close Is Close Enough?. Issue 1 (June 2015) - Hillis, James M.; Thielen, James; Tibbits, Josh; Lathrop, Art; Lamb, Dave; Derlofske, John Van
Abstract : How close do color primaries have to be to the ITU Rec. 2020 recommendations to qualify as meeting this standard? Ideally, qualification would mean perceptual equivalence. Perceptual equivalence is, however, task dependent. In this paper, we present discrimination thresholds for colors near the Rec. 2020 boundary. We use these data to discuss guidelines to qualify displays as meeting the Rec. 2020 standard.